INTROGRESSION OF A BROWN NORWAY CHROMOSOME 2 FRAGMENT INTO DAHL SALT-SENSITIVE RATS EXERTS ANTI- AND PRO-INFLAMMATORY EFFECTS UNDER A NORMAL AND HIGH-SALT DIET, RESPECTIVELY. (April 2021) - Berillo, Olga; Ouerd, Sofiane; Rehman, Asia; Richer, Chantal; Sinnett, Daniel; Kwitek, Anne E.; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : Objective: Chromosome 2 (Chr2) introgression from normotensive Brown Norway (BN) rats into hypertensive Dahl salt-sensitive (SS) background (SB2) reduced blood pressure (BP) and vascular inflammation under normal-salt diet (NSD). We hypothesized that BN Chr2 contains anti-inflammatory genes that could reduce BP elevation and vascular inflammation in rats fed NSD and high-salt diet (HSD). Design and method: Four- to 6-week-old male SS and congenic rats containing the BN Chr2 distal (SB2a) and middle segment (SB2b) were fed NSD or HSD (4% NaCl) for 8 weeks. BP was determined by telemetry, reactive oxygen species generation using dihydroethidium staining, and vascular cell adhesion molecule 1 and monocyte chemoattractant protein-1 expression and monocyte/macrophage infiltration by immunofluorescence in aorta or perivascular fat. RNA was extracted from aorta and used for small and total RNA-sequencing. Differentially expressed genes (DEGs) were identified with fold change > 1.3 and fold discovery rate < 0.05 and some of them were validated with reverse transcription-quantitative PCR (RT-qPCR). Results: SS Systolic BP was 145 ± 2 mm Hg under NSD and 168 ± 1 mm Hg under HSD, which was lower in SB2a and SB2b SBP (125 ± 3 and 127 ± 6, P < 0.05) under NSD but similar under HSD. Examination of inflammation markers revealed that SB2a presented less and more inflammation under NSD and HSD, respectively, compared to SS. DEGs were identified in SB2a vs. SS uniquely under NSD (27) and HSD (608) and under both diet (7), and in SB2b vs. SS uniquely under NSD (133) and HSD (9) and under both diet (12). DEGs encoded within BN Chr2a were identified uniquely under NSD (2) and HSD (8), and in both diets (3). RNA-sequencing and RT-qPCR validation identified two DEGs encoded within BN Chr2 distal segment that could play a role in the vascular inflammation. These were down-regulated glutamyl aminopeptidase (Enpep) that was anti-inflammatory under NSD and up-regulated heparan sulfate 2-O-sulfotransferase 1 (Hs2st1) that was pro-inflammatory under HSD. Conclusions: Two DEGs encoded within introgressed BN Chr2 distal segment were identified: Enpep associated with decreased vascular inflammation under NSD, and Hs2st1, associated with elevated vascular inflammation under HSD.